Analisis Faktor Ketertatikan Desa Wisata Melalui Sarana Bumber Boad Menggunakan Metode SPSS - Anauta lungiding A.R.; Triyanti Irmiyana; Windra Iswidodo; Taufan Prasetyo; Retno Syahriawati Dewi (Pusat Riset dan Inovasi Nasional, 2023)
Sampang Regency has tourism potential, one of which is the Klampis Reservoir in Kedundung Village. Reservoir with an area of ​​approximately 1 hectare is a catchment area that has not been properly optimized by the community. This condition is exacerbated by the presence of wild plants that disturb the view. So that this research provides an innovation in the form of a source boad suggestion. To support the facilities, an analysis of the factors of tourist interest in visiting is carried out in order to synchronize the needs of the community with the invasion given. The method used is SPSS to improve quality and improve the quality of a variable. This method uses analysis of questionnaire data. This study uses 30 questionnaire samples to strengthen the results of the analysis. The purpose of this study is to find out the factors that most influence the sustainability of the tourist village area through the means of bounty boad. The results of the research on factors that can influence are the availability of facilities and infrastructure with an average total value of 500.